ANALISIS DETERMINAN BIAYA TRANSAKSI PETANI TAMBAK UDANG DALAM PERSPEKTIF EKONOMI ISLAM (STUDI DI KABUPATEN OGAN KOMERING ILIR, SUMATERA SELATAN) - Cahyani, Dita; Noviarita, Heni; Setyanto, Alief Rakhman (HUMAN FALAH: Jurnal Ekonomi dan Bisnis Islam, 2025)
The purpose of this research is to identify and analyze the determinants of shrimp farming transaction costs in Islamic economics. This research is included in the quantitative research category. The types of data used in this study consist of primary and secondary data. The population includes all shrimp farming farmers who run shrimp farming businesses in Ogan Komering Ilir Regency, South Sumatra, who are actively involved in farming activities and buying and selling shrimp farming products. The research sample is 100 shrimp farming farmers. The results of the social capital research amounted to t-count (-0.292729) < t-table (±1.992) the social capital variable did not have a significant effect on the transaction costs of shrimp farmers, the institutional variable did not have a significant effect on the transaction costs of shrimp farmers with t-count (-0.884217) < t-table (±1.992), transaction costs that occur among shrimp farmers with t-count (-2.431228) < t-table (-1.992), trust did not have a significant effect on the transaction costs of shrimp farmers with t-count (1.639753) < t-table (1.992), and uncertainty did not have a significant effect on the transaction costs of shrimp farmers with t-count (0.250817) < t-table (1.992).